Thinning Practice in the Andamans - Past, Present and Proposed - D'cruz, A. C. (Indian Forester, 1953)
This paper is a review of thinning practice in the Andamans, showing the change-over from sylvicultural crown thinnings to elite thinnings which have been found to be most aptly suited to conditions prevailing in these islands. Elite thinnings have been started only from 1952 and on experience gained through the years, this Forest Department, plans to formulate a thinning practice of its own, based on the elite pattern.